Real-World Efficacy and Safety of Anlotinib With and Without Immunotherapy in Advanced Non-Small Cell Lung Cancer - Xiong, Qi; Qin, Boyu; Xin, Lingli; Yang, Bo; Song, Qi; Wang, Yu; Zhang, Sujie; Hu, Yi (Frontiers in Oncology, 2021)
Aims Combination of anti-angiogenesis therapy and immunotherapy has showed synergistic effects in non-small cell lung cancer (NSCLC). The aim of this retrospective study was to investigate the efficacy and safety of anlotinib with and without immunotherapy in NSCLC. Methods Pathologically confirmed NSCLC patients (stage IIIB-IV) receiving anlotinib between November 2018 and February 2020 were enrolled for retrospective analysis. The outcomes and safety of overall patients were evaluated, and the efficacies of anlotinib plus immunotherapy and anlotinib alone was compared. The primary endpoint was progression-free survival (PFS). Results A total of 80 patients (median age: 62 years, range: 29-86 years) were included. Overall median PFS was 4.3 months (95% confidence interval (CI): 2.7-5.9 months). In univariate analysis, patients without EGFR mutation, previous EGFR target therapy, and brain metastasis had significantly longer PFS. Cox regression analysis showed that only brain metastasis was an independent predictor of PFS. The median PFS of patients receiving anlotinib plus immunotherapy was slightly longer than that of patients receiving anlotinib alone (4.2 vs 3.1 months); however, the difference was not statistically significant. A tendency of longer median PFS was observed in patients with adenocarcinoma, EGFR wild type, stage IV, no liver metastasis, former smoker, ≥2 previous treatment lines, no previous VEGF or EGFR target therapies in anlotinib plus immunotherapy group. Treatments with anlotinib alone or anlotinib plus immunotherapy were well tolerable. The most common adverse events were fatigue, decreased hemoglobin count, hypertension, hand-foot syndrome, oral mucositis and hoarseness. Conclusion Anlotinib is well tolerable and effective in advanced NSCLC patients. Brain metastasis is an independent predictor of PFS in NSCLC patients receiving anlotinib. Future prospective studies with larger sample size and extended follow-up are needed to confirm the clinical benefit in NSCLC patients treated with anlotinib combined with immunotherapy.